2021
DOI: 10.1055/a-1393-8302
|View full text |Cite
|
Sign up to set email alerts
|

Management of Disseminated Intravascular Coagulation in Acute Leukemias

Abstract: Disseminated intravascular coagulation (DIC) is characterized by the intravascular activation of coagulation with loss of localization arising from different causes, and is diagnosed using scoring systems which rely upon the presence of an underlying disorder compatible with DIC alongside hemostatic derangements such as low platelet count, prolonged prothrombin time, and elevated fibrinogen degradation products. DIC is common in patients with acute leukemia, with prevalence ranging from 17 to 100% in acute pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…When leukocytes in the peripheral blood are normal, coagulopathy may be a clue to the diagnosis of AL. Acute promyelocytic leukemia (APL) has a high frequency of coagulopathy, with a DIC complication rate of 78.0% compared to 31.6% for AML excluding APL [ 12 ]. Although this case was diagnosed as AML cuplike, a report of the same type of cases showed a DIC complication rate of 57.1%, suggesting that this type of patient may be prone to DIC as well as APL [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…When leukocytes in the peripheral blood are normal, coagulopathy may be a clue to the diagnosis of AL. Acute promyelocytic leukemia (APL) has a high frequency of coagulopathy, with a DIC complication rate of 78.0% compared to 31.6% for AML excluding APL [ 12 ]. Although this case was diagnosed as AML cuplike, a report of the same type of cases showed a DIC complication rate of 57.1%, suggesting that this type of patient may be prone to DIC as well as APL [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not initially do so, we recommend considering checking D-dimer levels in the evaluation of newly diagnosed AML patients. DIC commonly occurs in the setting of BCS due to APL with prevalence ranging from 17% to 100% [ 7 , 11 , 21 ]. DIC is mainly associated with bleeding in APL, while thrombosis is common in acute lymphocytic leukemia (ALL) and non-APL AML [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…DIC commonly occurs in the setting of BCS due to APL with prevalence ranging from 17% to 100% [ 7 , 11 , 21 ]. DIC is mainly associated with bleeding in APL, while thrombosis is common in acute lymphocytic leukemia (ALL) and non-APL AML [ 21 ]. In the study reported by Amitrano et al [ 7 ] of BCS due to non-promyelocytic AML, no DIC was reported; however, in our case, DIC was suspected due to the patient having both clinical (hepatic vein thrombosis) and laboratory findings consistent with DIC.…”
Section: Discussionmentioning
confidence: 99%
“…Acute leukemia is frequently complicated with DIC, with up to 100% prevalence in acute promyelocytic leukemia (APL) and between 8.5 and 25% in acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). 76 In APL, high levels of annexin II on leukemic cells are responsible for the upregulation of the fibrinolytic system. 77 Annexin II has a high affinity for both plasminogen and its activator tissue-type plasminogen activator (t-PA), and facilitates plasminogen activation leading to increased fibrinolysis.…”
Section: Bleeding-type Disseminated Intravascular Coagulationmentioning
confidence: 99%